IMPROVEMENT OF SURFACE CHARGING QUALITY WITH KNURLING TOOL BY IMPARTING ULTRASONIC OSCILLATIONS TO IT - M. G. Kiselev; A. V. Drozdov; V. L. Drozdov; M. S. Gurinovich (Наука и техника)
The paper contains results of experimental investigations reflecting the impact of technological and acoustic parameters on abrasive ability and resistance period of diamond-containing coating. Such  coating has been obtained on the disk surface as a result of its charging with a knurling tool under normal conditions and imparting ultrasonic oscillations to it.